High K(+)-Induced Relaxation by Nitric Oxide in Human Gastric Fundus - Kim, Dae Hoon (The Korean Physiological Society and The Korean Society of Pharmacology, 2012)
This study was designed to elucidate high K(+)-induced relaxation in the human gastric fundus. Circular smooth muscle from the human gastric fundus greater curvature showed stretch-dependent high K(+) (50 mM)-induced contractions. However, longitudinal smooth muscle produced stretch-dependent high K(+)-induced relaxation. We investigated several relaxation mechanisms to understand the reason for the discrepancy. Protein kinase inhibitors such as KT 5823 (1 µM) and KT 5720 (1 µM) which block protein kinases (PKG and PKA) had no effect on high K(+)-induced relaxation. K(+) channel blockers except 4-aminopyridine (4-AP), a voltage-dependent K(+) channel (K(V)) blocker, did not affect high K(+)-induced relaxation. However, N(G)-nitro-L-arginine and 1H-(1,2,4)oxadiazolo (4,3-A)quinoxalin-1-one, an inhibitors of soluble guanylate cyclase (sGC) and 4-AP inhibited relaxation and reversed relaxation to contraction. High K(+)-induced relaxation of the human gastric fundus was observed only in the longitudinal muscles from the greater curvature. These data suggest that the longitudinal muscle of the human gastric fundus greater curvature produced high K(+)-induced relaxation that was activated by the nitric oxide/sGC pathway through a K(V) channel-dependent mechanism.